Ruta graveolens: Boost Melanogenic Effects and Protection against Oxidative Damage in Melanocytes - Pazilaiti Ainiwaer; Zuopeng Li; Deng Zang; Lan Jiang; Guoan Zou; Haji Akber Aisa (MDPI AG, 2023)
Vitiligo, an acquired depigmentation disorder, is characterized by the loss of functional melanocytes and epidermal melanin. In recent years, research has focused on promoting melanin biosynthesis and protecting melanocytes to reduce stress-related damage for the purpose of applying it to vitiligo treatment. Ruta graveolens L. has been utilized as a medicinal herb in diverse traditional medicine systems to address conditions like vitiligo. In this investigation, we isolated and purified 16 unique alkaloid compounds from the chloroform extracts of R. graveolens, encompassing a new quinoline alkaloid and several recognized compounds. Bioactivity analysis showed that compound 13, an alkaloid derived from R. graveolens, promotes melanin production while protecting PIG3V melanocytes against 4-tert-butylphenol (4-TBP)-induced oxidative damage by downregulating endoplasmic reticulum (ER) stress and pro-inflammatory cytokines through interleukin-6 (IL-6) regulation. Additionally, the compound suppressed the expression of Bip, IRE1, p-IRE1, and XBP-1 proteins, suggesting a potential antioxidant function. These findings suggest that compound 13 isolated from R. graveolens can augment melanogenesis in melanocytes, reduce endoplasmic reticulum (ER) stress, and ameliorate vitiligo exacerbation. The melanogenic activity observed in the chloroform fraction emphasizes R. graveolens's potential as a novel therapeutic target for vitiligo treatment, warranting further exploration in future studies.